Re-membering the Saints: A Contextual Interpretation of the Early Christian Relic Shrine Beneath the Church of SS. Giovanni e Paolo in Rome - Munk, Ana (2008)
“The phenomenon of relics was characterized by an insistent impulse toward figuration, ” writes Patricia Cox Miller in a discussion on primarily Late Antique literary arts. The 4th century relic shrine found beneath the church of SS Giovanni e Paolo in Rome is a rare example a persistent desire to formulate the presence of relics using pictorial means. Unlike other known examples of martyrs’ shrines which were found in the catacombs or extramural locations, this shrine was found in the domus of a Christian senator named Pammachius. The shrine’s unique location and visual content---since it is the first known example of a pictorial hagiographical narrative--raises questions of its function in a private setting, its patronage, and its audience use and reception. This presentation proposes to recreate the context for this shrine by focusing on the profile of its patrons. Such an approach is justified since the relic figuration was propelled by the intense physical and emotional closeness that the Early Christians felt toward the remains of the martyrs, as testified by the contemporary poems of Prudentius as well as the writings and practices of the Early Christians who belonged to the same social network as Senator Pammachius. The most striking aspect of this social network is their adherence to ascetic practices within the self-imposed confinements of their lavish homes. How these aristocrats-turned-saints appropriated and visualized sainthood in their homes is what this presentation hopes to shed light on.